Influence of mechanical activation on the oil composition and on characteristics of its fraction boiling away above 500ºС - S. V. Ivanov; P. S. Antonyuk; V. A. Lutskovskaya; V. V. Kravchenko; S. I. Vorob’ev; V. N. Torkhovskij (Тонкие химические технологии, 2010)
The pressure effect in the disintegration unit DA-1 on the oil has been investigated. A change in oil composition and indicators characterizing some properties of the residual fraction of direct distillation has been identified.